(untitled) (Konferensiyalar | Conferences, 2024)
Currently, the primary objective in foreign language education is to develop proficiency in speaking the language. Many countries, including the Republic of Uzbekistan, have incorporated foreign language instruction into the primary school curriculum. This thesis explores various aspects of enhancing speaking skills in primary grades through the utilization of nontraditional technologies.